Efficacy and Safety of Gliclazide versus Glimepiride in T2DM Patients: A Systematic Review - Rifika Bansal; Ravi Kant; Yogesh Bahurupi; Ashwarya Gupta (Indian Journal of Endocrinology and Metabolism, 2025)
This systematic review compares the efficacy and safety of gliclazide and glimepiride in managing type 2 diabetes mellitus (T2DM). A comprehensive search was conducted in multiple databases, including PubMed and Cochrane Library, to identify relevant randomised controlled trials and observational studies. Five studies were included based on pre-defined eligibility criteria, focussing on glycaemic control (HbA1c, fasting blood glucose, and post-prandial blood glucose) and safety outcomes like hypoglycaemia and cardiovascular events. Data were extracted and synthesised using established systematic review methodologies, and risk of bias was assessed with Cochrane tools. Both gliclazide and glimepiride effectively reduced HbA1c, but gliclazide showed a lower risk of hypoglycaemia. However, elderly patients using gliclazide had an increased risk of severe hypoglycaemia and fractures. This review indicates that while both drugs are effective, gliclazide may have a safer profile in middle-aged adults, with glimepiride potentially being a better option for older adults.